Nonanthropocentrism in the view of deep ecology - Mateja-Furmanik, Magdalena (Hybris, 2019)
The growing concern over the state of environment pollution, depletion of natural resources, diminishing Arctic polar ice cap, to name just a few, has led to escalating interest in ecological movements. While "shallow ecology movements" focus on developing technological solutions or fight for protection on the level of administration, deep ecology goes to the root of the global environmental crisis which is the human worldview. In this paper I describe how the notion of anthropocentrism evolved and its implications with particular focus on the conception of the great chain of beings, which is considered as underlying thought pattern of Western Culture. Later on I present the alternative view of deep ecology with its notions of environment as a net of intrinsic relations, ecological self as well as biospheric egalitarianism.